Issue information - Studies in Communication Sciences (Studies in Communication Sciences, 2018)
SComS is an international open access journal of communication research that is jointly edited by the Swiss Association of Communication and Media Research (SACMR) and the Faculty of Communication Sciences of the Università della Svizzera italiana (USI Lugano). It is published twice a year with the support of the Swiss Academy of Humanities and Social Sciences (SAHS).